Thermal dispersion method for an ultrasonic phased-array transducer. (20th June 2016) - Choi, Euna; Lee, Wonseok; Roh, Yongrae
Abstract: When the driving voltage of an ultrasonic transducer is increased to improve the quality of ultrasound images, heat is generated inside the transducer, which can burn the patient's skin and degrade transducer performance. In this study, the method to disperse the heat inside an ultrasonic phased-array transducer has been examined. The mechanism of temperature rise due to heat generation inside the transducer was investigated by numerical analysis and the effects of the thermal properties of the components of the transducer such as specific heat and thermal conductivity on the temperature rise were analyzed. On the basis of the results, a heat-dispersive structure was devised to reduce the temperature at the surface of the acoustic lens of the transducer. Prototype transducers were fabricated to check the efficacy of the heat-dispersive structure. By experiments, we have confirmed that the new heat-dispersive structure can reduce the internal temperature by as much as 50% in comparison with the conventional structure, which confirms the validity of the thermal dispersion mechanism developed in this work.